2005
DOI: 10.1002/app.21595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosized calcium carbonate on the mechanical properties of latex films

Abstract: An acrylic dispersed nanosized calcium carbonate filler was added to a prevulcanized latex compound in different amounts. The effect of filler content on the curing time, modulus, tensile strength, elongation at break (Eb) before and after ageing, and the morphology of the films was investigated. Results showed that the curing time decreased with filler loading because of the increased interaction between the filler and rubber matrix, as reflected by the decrease in the apparent swelling index. Modulus at 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…That was identified as the coalescence of latex particles during gelation which tend to get adversely affected by over curing . Manroshan and Baharin have explained the findings on tensile properties of nanosized CaCO 3 filled NR latex films supporting the hypothesis suggested by Presis et al The reduced tensile strength at higher loading of filler is attributed to filler‐filler interaction which goes beyond the enhanced filler–rubber interactions . Cai et al also reported that when the filler loading continued to increase above the critical level where the contacts of rubber to filler tends to be saturated, the distance between rubber particles is increased.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…That was identified as the coalescence of latex particles during gelation which tend to get adversely affected by over curing . Manroshan and Baharin have explained the findings on tensile properties of nanosized CaCO 3 filled NR latex films supporting the hypothesis suggested by Presis et al The reduced tensile strength at higher loading of filler is attributed to filler‐filler interaction which goes beyond the enhanced filler–rubber interactions . Cai et al also reported that when the filler loading continued to increase above the critical level where the contacts of rubber to filler tends to be saturated, the distance between rubber particles is increased.…”
Section: Resultsmentioning
confidence: 68%
“…Direct reinforcement of latex is one of the most long standing problems faced by the latex technologists, especially in NRL based processes. Silica, silica derivatives, clay, calcium carbonate, and banana stem powder are some of the experimented nonblack fillers for NRL. However there is no established, practical method available in commercial scale for the reinforcement of NRL films though it is well established in dry rubber processes.…”
Section: Introductionmentioning
confidence: 99%
“…Os polímeros nitrílicos são amorfos, não cristalinos, e necessitam de cargas de reforço para que suas propriedades sejam otimizadas [5,6] . O sistema borracha/reforço, como borracha/cargas inorgânicas [7][8][9] , e no caso especial borracha/fibras, podem ser considerados compósitos que combinam a resistência e rigidez do reforço com o comportamento elástico da borracha [10] .…”
Section: Métodosunclassified
“…layered silicates). However, nanoparticles can hardly be dispersed uniformly owing to their tendency for agglomeration, which occurs especially at higher filler volume fractions [18,27]. Thus, property deterioration is usually observed with increasing filler content [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Coagulating rubber latex and aqueous dispersion of clay is proven to be a simple technique for obtaining films of high strength and tear resistance [10][11][12][13][14][15][16]. Calcium carbonate particles have also been used to improve the mechanical performance of latex products [17][18][19]. On the other hand, carbon black has received less attention as reinforcing filler [20], opposed to silica grades [21][22][23][24][25], due to its hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%